A new image scrambling approach using block-based on shifted algorithm - Abugharsa, Ahmed Bashir; Hasan Basari, Abd Samad; Almangush, Hamida (AJBAS, 2013)
Image scrambling is a useful approach to secure the image data by scrambling the image into an unintelligible format. This paper proposes a new scramble algorithm which can be produced by a series of shifting the rows and the columns. The first part of the algorithm aims to build a shifted table using hash function within scramble phase and descramble phase to generate an scrambled (shifted) image and the retrieved image. The second part of the algorithm uses the shifted table resulted from the first part of the algorithm to generate newly shifted image (Scrambled) in which the rows and the columns of the original image are shifted. This makes the scrambled images difficult to decode thus providing a high level of security protection for the images. The results show that the correlation between image elements has been significantly decreased using the proposed technique, and higher entropy has been achieved. Furthermore, implies a high similarity and a good quality of the retrieved image compared to the original image. The algorithm can be applied in the real-time applications since it is a straightforward process and easily implemented.